Mothering Practices of Filipino Generation Z: Correlations with Personal Characteristics and State of Well-being - Bermal, Marian Lucille N.; Gaerlan, Paolo Miguel S.; Suarez, Jesley Eryne E.; Alberto, Raziel Alodia L.; Arcinas, Myla M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study aimed to describe authoritative Filipino Generation Z mothers' mothering practices, including their concept of authority, parent-child communication, and reward-punishment practices. Eighty (80) Gen Z mothers, ages 18 to 24, with at least one child, completed a self-administered questionnaire using purposive and snowball sampling. The findings indicated that mothers have highly authoritative parenting styles and have very healthy overall well-being. The mother's completed education level showed weak inverse correlations with parent-child communication (r = -0.432, p = 0.000) and concept of authority (r = -0.283, p = 0.011). The mother's monthly income had a weak inverse relationship with her concept of authority (r = -0.269, p = 0.016). Furthermore, the number of household members had weak inverse correlation with parent-child communication (r = -0.227, p = 0.042) and positive correlations with reward and punishment practices (r = 0.437, p = 0.000). Results imply that mothers with a lower level of education value more authority and communication with their children. The findings show weak negative correlations between the mother's concept of authority and social well-being (r = -0.289, p = 0.009), implying that less concern for authority meant better social health. Furthermore, open lines of communication between mother and child have positive effects on their psychological health (r = 0.380, p = 0.001). Rewarding has shown to improve their psychological health (r = 0.257, p = 0.021) and overall well-being (r = 0.232, p = 0.038). The results could promote strategies that make Gen Z mothers use effective mothering practices in child-rearing.